Pendidikan Karakter Anak Usia Dini dalam Menghadapi Tantangan Pola Asuh Generasi Strawberry menurut Perspektif Islam - Imas Jihan Syah; Diana Dwi Jayanti; Mohammad Luthfillah (Universitas Islam Lamongan, 2024)
Character building in educational process is a fundamental element for forming the personality and morality of the younger generation. However, increasingly rapid and complex developments have presented their own challenges in implementing parenting patterns for children. One of these challenges is the emergence of a phenomenon called the “Strawberry generation”. This term refers to a generation that appears fragile, gives up easily, and lacks resilience in facing life's pressures or difficulties. One of the reasons for this is that parenting styles tend to be excessive in providing comfort without instilling the values ​​of toughness and independence. Facing this challenge, a character education strategy is needed that can form children who not only have intellectual intelligence, but also mental strength and good morals. The Islamic perspective, with its emphasis on the moral and spiritual values ​​contained in the teachings of the Qur'an and Hadith, offers a relevant approach to shaping the character of the younger generation. This research aims to explore character education strategies in facing parenting challenges in the strawberry generation, by examining the Islamic perspective which focuses on the formation of children's morals and mental resilience. The approach used in this research is a literature review with qualitative analysis of sources related to character education, parenting patterns and related Islamic teachings. The results of the study show that in Islam, character education does not only focus on teaching morals and ethics, but also prioritizes developing the traits of self-resilience, such as patience (shabr), steadfastness (istiqamah), and trust in Allah. Apart from that, the parenting style taught in Islam emphasizes a balance between deep love and strict application of discipline, as exemplified by the Prophet Muhammad SAW. Thus, it is hoped that the character education strategy from an Islamic perspective can be a solution to overcome the weaknesses of the strawberry generation, as well as form a young generation who is tough, has noble character, and is ready to face life's challenges with full confidence.